Hydrochemical features of groundwater from aquifer systems occurring near central São Paulo state, Brazil - Bonotto, Daniel Marcos [UNESP]; Mancini, Luis Henrique; Tonetto, Érica Martini (My University, 2012)
Brazil owns the highest availability of renewable hydrological resources in world. However, in the beginning of the 21st century, it was the 26th country in terms of social water availability as a consequence of the great unequal distribution of the hydrological resources in the country. This is because it is mainly concentrated in northern and portions of northeastern and central western regions, where the population density is low. This advanced degree of unequal water distribution has caused special attention to the groundwater resources due to problems related to the interaction between the society and the environment. São Paulo is the most populous Brazilian state, comprising ~ 40 million inhabitants distributed over 645 municipalities. It has the highest number of industries and economic production, reaching 31% of the Brazilian GDPgross domestic product. Despite the vigorous industrial production that includes high technology goods, the state also is well developed in agriculture and cattle breeding. This advanced stage of agricultural and industrial growth causes to São Paulo State an accentuated use of groundwater resources in water-supply systems. Several lithologies of the Paraná sedimentary basin outcrop in São Paulo State. They consist on sandstones, conglomerates, diamictites, tillites, siltstones, mudstones, limestones, shales, silex, rythmites, basalts, diabases and different types of Cenozoic covers like the recent deposits, terrace sediments and the Rio Claro Formation (sandstones, conglomerate sandstones and muddy sandstones). Many of these rock types are important reservoirs for groundwater in São Paulo State. Rio Claro city is located at the northeastern edge of the Paraná basin, cropping-out several units of the basin in the region. Rio Claro city is the most important municipality in Corumbataí River basin that extends over an area of about 1581 km2. The area considered in this chapter includes Rio Claro city and portions of Araras, Leme, Cordeirópolis, Santa Gertrudes, Itirapina, Corumbataí and Ipeúna municipalities. Different groundwater systems have been focused in this chapter, among them: a phreatic aquifer comprising a cover of unconsolidated materials from Rio Claro Formation; sediments from Tubarão Group, comprising a confined aquifer about 40 m thick; deep bodies of diabase that store water within their fractures. In general, sedimentary aquifers exhibit different flow and hydrochemical characteristics in relation to that of the fractured rock aquifers and these aspects will be considered in this chapter. © 2012 Nova Science Publishers, Inc. All rights reserved.